The Use of Agile and Scrum Methods in the Implementation of Advertising Media Construction Projects Reviewed from Time Limitations and Project Locations Adjacent to Cultural Heritage Buildings - Al Qordhowi, Andrian Firdaus Yusuf (Electronic Journal of Education, Social Economics and Technology, 2025)
The project by PT Adhi Kartika Jaya, JJ Promotion, is a high-value investment project on Jalan Kertajaya Surabaya, near the Cultural Heritage Building Viaduc Kertajaya. The project aims to install outdoor billboards with a strategic location and work hours between 00:00 WIB and 06:00 WIB. To achieve expected results, construction management over existing resource assets is crucial. The project must focus on preventing damage to cultural heritage buildings, implementing K3 (Occupational Health and Safety) aspects, and completing on time. Thorough documentation is necessary to identify vulnerable points and ensure safety equipment is used. The project is divided into two main stages: backlog/stage in the workshop and backlog/stage at the project site. After completion, the project area is cleaned and inspected to ensure safety. The project serves as a lesson for exploring broader project management knowledge, such as the Agile Method with Scrum and Kanban tools.